2013
DOI: 10.1111/anu.12005
|View full text |Cite
|
Sign up to set email alerts
|

Total fish meal replacement with canola protein isolate in diets fed to rainbow trout (Oncorhynchus mykissW.)

Abstract: The potential of canola protein isolate (CPI) as fish meal alternative in diets for rainbow trout was evaluated. Apparent digestibility coefficients (ADCs) for protein from a fish meal-based reference diet (89.2 ± 1.1%) and CPI (84.6 ± 1.8%) were determined by indirect marker method in a digestibility experiment. ADC of dietary dry matter was slightly lower for the reference diet (62.5 ± 4.7%), but not significantly different to the CPI test diet (65.9 ± 3.1%). In a subsequent growth trial, 20 fish (initial we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
3
22
2
1
Order By: Relevance
“…Rather, the RPI 100 fed group recorded the highest feed intake, though not differ from other fed groups, indicating that diets palatability and acceptability were not affected. Our findings are in consonant with Slawski et al (2013) and Kumar et al (2012), who observed no significant difference in the feed intake of rainbow trout and common carp fed canola and jatropha protein isolates, respectively. Sharma et al (2014) reported that feeding RKM diets containing a high level of cyanide (>39 mg kg −1 ) to rohu led to a reduction in protein utilization and digestion processes, which resulted in poor growth performance.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Rather, the RPI 100 fed group recorded the highest feed intake, though not differ from other fed groups, indicating that diets palatability and acceptability were not affected. Our findings are in consonant with Slawski et al (2013) and Kumar et al (2012), who observed no significant difference in the feed intake of rainbow trout and common carp fed canola and jatropha protein isolates, respectively. Sharma et al (2014) reported that feeding RKM diets containing a high level of cyanide (>39 mg kg −1 ) to rohu led to a reduction in protein utilization and digestion processes, which resulted in poor growth performance.…”
Section: Discussionsupporting
confidence: 91%
“…The variation in their results may be due to the levels of ANFs, nonstarch polysaccharide, and or species differences. Literature have shown that varying level of antimetabolites, indigestible carbohydrates, amino acid imbalances and other complexes may contribute to growth depression often observed when plant protein ingredients are fed at higher inclusion levels to fish, rather than pinpointing one single factor as the primary reason for the adverse effects noticed (Mambrini et al, 1999;Francis and Becker, 2001;Schulz et al, 2007;Slawski et al, 2013;Shamna et al, 2015). However, in the present study, no significant variation was observed in the growth performance of the fish fed RPI in replacement for SPI.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations